2017
DOI: 10.1038/cddiscovery.2016.96
|View full text |Cite
|
Sign up to set email alerts
|

Matrine induces RIP3-dependent necroptosis in cholangiocarcinoma cells

Abstract: The development of acquired resistance to pro-apoptotic antitumor agents is a major impediment to the cure of cholangiocarcinoma (CCA). Antitumor drugs inducing non-apoptotic cell death are considered as a new approach to overcome such drug resistance. Here, we reported for the first time that matrine-induced necroptosis in CCA cell lines, differing from its classical role to induce apoptosis in many other kinds of cancer cells. CCA cells under matrine treatment exhibited typical necrosislike but not apoptotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 42 publications
1
50
0
Order By: Relevance
“…Our data demonstrated morphological necroptosis signs in U-87 MG cells after treating with 30 μM LyeTx I-b, characterized by the swelling of nucleus and mitochondria, increase in cytoplasm volume, membrane disruption, cytoplasm vacuoles, and release of cellular content. Other studies using TEM showed necroptosis signs after treatment with natural alkaloid compounds (martine) in cholangiocarcinoma cells (CCA) characterized by cytoplasmic vacuolation and extensive swelling of organelle and loss of plasma membrane integrity (Xu et al 2017). As a consequence of cellular swelling and rupture of the plasma membrane, they also observed an extravasation of cellular components and increase in LDH, as observed in the present study (Zhao et al 2016).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our data demonstrated morphological necroptosis signs in U-87 MG cells after treating with 30 μM LyeTx I-b, characterized by the swelling of nucleus and mitochondria, increase in cytoplasm volume, membrane disruption, cytoplasm vacuoles, and release of cellular content. Other studies using TEM showed necroptosis signs after treatment with natural alkaloid compounds (martine) in cholangiocarcinoma cells (CCA) characterized by cytoplasmic vacuolation and extensive swelling of organelle and loss of plasma membrane integrity (Xu et al 2017). As a consequence of cellular swelling and rupture of the plasma membrane, they also observed an extravasation of cellular components and increase in LDH, as observed in the present study (Zhao et al 2016).…”
Section: Discussionsupporting
confidence: 84%
“…In addition, morphological features of necroptosis are characterized by nucleus swelling, mild DNA condensation, and increased permeability of lysosomal and plasma membranes (Su et al 2016). Necroptosis can also be induced after treatment with chemotherapeutic agents (Xu et al 2017;Galluzzi et al 2011). Thus, induction of necroptosis could be a promising therapeutic strategy to overcome drug resistance (Su et al 2016;Pasparakis and Vandenabeele 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is critical to further investigate the expression of key necroptotic proteins and the level of phosphorylated MLKL, a specific marker of necroptosis in CCA clinical specimens. The analysis of RIPK3 expression in CCA primary tissues by immunohistochemistry has been previously reported, but RIPK3 protein was expressed in most CCA tissues, with lower levels in tumor tissues than in the paired normal liver tissues [63]. This may be because the previously reported study used paired normal liver tissues instead of paired normal cholangiocytes.…”
Section: Discussionmentioning
confidence: 89%
“…They also proved that the administration of a Smac mimetic could sensitize CCA cells to a low dose of standard chemotherapy with gemcitabine, by increasing TNFα mRNA levels and reversing gemcitabine-induced cell cycle arrest, leading to CD [122]. Xu et al reported, for the first time, that matrine, an alkaloid isolated from traditional Chinese medicine Sophora flavescens, induced necroptosis in CCA cell lines, differing from its classical role of inducing apoptosis in many other types of cancer cells [123]. The authors showed that CCA cells under matrine treatment exhibited a typical necrosis-like morphology instead of apoptotic changes, and that these effects were greatly attenuated by Nec-1, but not by the apoptosis inhibitor zVAD [123].…”
Section: Necroptosis-based Therapies For Cholangiocarcinomamentioning
confidence: 99%
“…Xu et al reported, for the first time, that matrine, an alkaloid isolated from traditional Chinese medicine Sophora flavescens, induced necroptosis in CCA cell lines, differing from its classical role of inducing apoptosis in many other types of cancer cells [123]. The authors showed that CCA cells under matrine treatment exhibited a typical necrosis-like morphology instead of apoptotic changes, and that these effects were greatly attenuated by Nec-1, but not by the apoptosis inhibitor zVAD [123]. A moderate expression of RIPK3 was observed in CCA cells and was required for matrine to induce necroptosis, which switched to apoptosis after endogenous R.…”
Section: Necroptosis-based Therapies For Cholangiocarcinomamentioning
confidence: 99%